Methods for extrapolating costs and effects in economic evaluations of telehealth interventions: a scoping review protocol - Søren Paaske Johnsen; Ulla Møller Weinreich; Sabine Michelsen Raunbak; Flemming Witt Udsen (BMJ Open)
Introduction Reviews of economic evaluations of telehealth interventions found that the current evidence is inconsistent with standard guidelines for conducting economic evaluation. The reviews conclude that most economic evaluations of telehealth interventions are small-scale and short-term. The choice of time horizon in economic evaluation, in general, is an important part. When using longer time horizons, it often involves extrapolating costs and effects, where assumptions are taken. Different tools for extrapolating cost and effects in economic evaluations exist. However, there is a heterogeneity in the methods used, which can create different results. Therefore, this study aims to review the design and conduct of existing long-term economic evaluations of telehealth interventions using extrapolation methods. Furthermore, the aim is to map the methods used for extrapolation.Methods and analysis A scoping review is conducted to investigate the aim of this study. To identify relevant studies for inclusion in the scoping review, a systematic literature search will be conducted in the electronic databases: Embase (Elsevier), PubMed (National Library of Medicine), EconLit (ProQuest), Web of Science (Clarivate), NHS Economic Evaluation Database (NHS Centre for Reviews and Dissemination) and CINAHL (EBSCO Industries). A grey literature search will be conducted in Google Scholar. The search will be supplemented with studies identified by reviewing the references in the included studies and reviewing the citations of the included studies. The extracted data from the studies in the scoping review will be presented in relevant descriptive tables and summarising descriptions. The results will be reported in correspondence with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews guideline.Ethics and dissemination Hence, the methodology used is a scoping review of the existing literature; no ethical or safety considerations are identified for this study. The plan for dissemination includes a peer-reviewed publication and possible poster or oral presentations.